ICAM-1-LFA-1 Dependent CD8+ T-Lymphocyte Aggregation in Tumor Tissue Prevents Recirculation to Draining Lymph Nodes - Yanguas, Alba; Garasa, Saray; Teijeira, Álvaro; Aubá, Cristina; Melero, Ignacio; Rouzaut, Ana (Frontiers in Immunology, 2018)
The quantity of T-lymphocytes reaching the draining lymph nodes from tumors is likely important to mount effective distant responses and for the establishment of long term systemic memory. Looking into mechanisms behind lymphocyte egress, we directed our attention to leukocyte adhesion mechanisms inside tumors. Here we demonstrate that activated T-cells form intra-tumor aggregates in a LFA-1-ICAM-1-dependent fashion in mouse models of melanoma and breast cancer. We also provide evidence of the presence of T-cell clusters in primary human melanoma. Disruption of LFA-1-ICAM-1 interactions, and thereby T-cell clustering, enhances the arrival of activated CD8+ T-cells to tumor draining lymph nodes in both transplanted and spontaneous cancer models. Interestingly, upon ICAM-1 blockade, the expression of the chemotactic receptor CCR7 augments in tumor infiltrating lymphocytes and in in-vitro de-clustered T cells, as well as their ability to transmigrate across lymphatic endothelial cells. We propose that ICAM-1-mediated homotypic T-lymphocyte aggregation may serve as a tumor-mediated immune retention mechanism entrapping activated CD8+ T cells in the tumor microenvironment. Modulation of T-cell adhesion may be of use to improve the transit of activated lymphocytes towards the lymph nodes and their subsequent recirculation.